2002
DOI: 10.1097/00002480-200211000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A Coronary Active Perfusion System for Off-Pump Coronary Artery Bypass: Advantage over Passive Perfusion Regarding the Physiology of the Coronary Artery

Abstract: To avoid myocardial ischemia during off-pump coronary artery bypass, we developed a coronary active perfusion system (CAPS) that perfuses arterial blood to the coronary artery at the diastolic phase of the cardiac cycle by a syringe pump system. We report herein the details and compare CAPS with a passive shunt circuit from the femoral artery (FA shunt), regarding the physiology of the coronary artery. Six pigs were used for this study. After CAPS or FA shunt perfusion was established, coronary flow and corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We proved that the coronary flow was approximately equal with the native coronary flow when we set the volume/beat of SAFE‐System to 0.2 mL/beat (7). In addition, we confirmed that the systolic pressure of the coronary artery was kept at 50–80 mm Hg when we set the volume/beat of SAFE‐System to 0.1–0.4 mL/beat (7). Based on these results, we decided to set the volume/beat of SAFE‐System to 0.1, 0.2, 0.3, and 0.4 mL/beat in this experiment.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…We proved that the coronary flow was approximately equal with the native coronary flow when we set the volume/beat of SAFE‐System to 0.2 mL/beat (7). In addition, we confirmed that the systolic pressure of the coronary artery was kept at 50–80 mm Hg when we set the volume/beat of SAFE‐System to 0.1–0.4 mL/beat (7). Based on these results, we decided to set the volume/beat of SAFE‐System to 0.1, 0.2, 0.3, and 0.4 mL/beat in this experiment.…”
Section: Methodsmentioning
confidence: 83%
“…Kamiya et al. reported that the coronary flow approximately maintained the native coronary flow when the volume/beat of SAFE‐System was set at 0.2 mL/beat (7). Based on this result, Watanabe et al.…”
Section: Discussionmentioning
confidence: 93%
“…To maintain myocardial perfusion during anastomoses, our originally developed coronary active perfusion system was used in all cases. [15][16][17] The most critical vessel-the LAD in most patients-was revascularized first to provide a backup to other areas. Distal anastomoses were performed with 8-0 polypropylene running sutures.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Studies examining the physiological effect of active versus passive distal coronary perfusion have shown that active distal coronary perfusion provides superior myocardial protection compared with passive perfusion. 31,32 …”
Section: Preventing Intraoperative Myocardial Ischemiamentioning
confidence: 99%